Student’s Science Literacy Skills with Problem Based Learning in Senior High School in Tanjungpinang - Nevrita Nevrita; Trisna Amelia; Desi Rahmatina (Bioeducation Journal, 2019)
The average national exam score of biology subject in high school in Tanjungpinang tends to be the lowest among other subjects. It is assumed that the ability of student science literacy also tends to be weak. The role of teacher is very important to improve student’s science literacy ability. Applying various learning strategies to create meaningful learning processes is one of the teacher's role. The strategy is Problem-based Learning (PBL) model. This research was conducted to determine science literacy ability of high school students in Tanjungpinang using PBL learning strategy. Research was conducted in SMA 4 and SMA 6 in Tanjungpinang. It is a quantitative approach with Quasi Experiment. PBL is free variable and science literacy skills as bound variable. Researcher uses tests, observation sheets and interviews as research instruments. Based on the results of this research can be concluded that implementation of PBL gives significant difference for student’s science literacy in tenth grade in SMA 4 and SMA 6.